In-vitro Antioxidant Potential of the Flavonoid Glycosides from Cassia tora linn. Leaves - Vijayalakshmi, A.; Jayakumari, S.; Masilamani, K. (Penerbit Universiti Malaysia Pahang, 2016)
The present study aimed to study the anti-oxidant potential of isolated flavonoids from the ethanol extract (70%v/v) of Cassia tora leaves. Three flavonoids were isolated viz Luteolin-7-O-β-glucopyranoside (I), quercetin-3-O-β-d-glucuronide (II) and Formononetin-7-O-β-D-Glucoside (III) from the ethanol extract (70%v/v) of Cassia tora leaves in the previous study. A comprehensive study on the phytochemical contents - total phenolic content and flavonoid content was accessed using Folin-Denis and AlCl3 method respectively. The antioxidant potential of the samples was evaluated using inhibition of hydroxyl radical, 2,2-diphenyl-1- picrylhydrazyl (DPPH), and nitric oxide scavenging methods. The total phenolic content and flavonoid content was found to be 18.60 % w/w and 9.5% w/w respectively. The IC50 values of ethanol extract against hydroxyl, DPPH and nitric oxide radical were found to be 270 µg/mL, 190 µg/mL and 130 µg/mL respectively. The radical scavenging activity of the isolated flavonoids decreased in the following order: quercetin (IC50 values 15, 14, 18 µg/mL) >formononetin (IC50 values 19, 21, 14 µg/mL) > luteolin (IC50 values 20, 23, 18 µg/mL) respectively. Index terms - Cassia tora, flavonoids, HPTLC, antioxidant